2016
DOI: 10.1038/oncsis.2015.51
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of EGFR–RAS signaling and nuclear localization of YBX1 in colorectal cancer

Abstract: The transcription factor YBX1 can act as a mediator of signals transmitted via the EGFR–RAS–MAPK axis. YBX1 expression has been associated with tumor progression and prognosis in multiple types of cancer. Immunohistochemical studies have revealed dependency between YBX1 expression and individual EGFR family members. We analyzed YBX1 and EGFR family proteins in a colorectal cancer (CRC) cohort and provide functional analyses of YBX1 in the context of EGFR–RAS–MAPK signaling. Immunohistochemistry for YBX1 and EG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The effect of the KRAS(G12V) mutation on cetuximab response was also tested in an isogenic cell system. Briefly, CaCo2 cells were stably transfected with a doxycycline-inducible KRAS-mutated plasmid [33], which allowed for conditional expression of mutated KRAS(G12V) (Figure 1B). To test the effect of KRAS(G12V), cells were treated with doxycycline (2 µg/mL) 24 h prior to treatment with cetuximab, which led to the expression of KRAS(G12V) (Figure 1B) in association with reduced cell proliferation (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the KRAS(G12V) mutation on cetuximab response was also tested in an isogenic cell system. Briefly, CaCo2 cells were stably transfected with a doxycycline-inducible KRAS-mutated plasmid [33], which allowed for conditional expression of mutated KRAS(G12V) (Figure 1B). To test the effect of KRAS(G12V), cells were treated with doxycycline (2 µg/mL) 24 h prior to treatment with cetuximab, which led to the expression of KRAS(G12V) (Figure 1B) in association with reduced cell proliferation (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…The colorectal cancer cell lines KRAS wild-type SW48 (ATCC, CCL-231), KRAS(G12V)-mutated SW480 (ATCC, CCL-228) and KRAS(G13D)-mutated HCT116 (ATCC, CCL-247) were used. Additionally, we used the colorectal carcinoma cell line CaCo2 that was stably transfected with doxycycline-inducible KRAS(G12V) [33]. The cells were cultured in Dulbecco’s modified Eagle’s medium (DMEM) (SW48, SW480) and in RPMI (HCT116) supplemented with 10% fetal calf serum (FCS) and 1% penicillin-streptomycin (PS).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that intracellular YB-1 activates Notch signalling [ 53 ] and acts as a mediator of signals transmitted via the EGFR-RAS-MAPK [ 54 ] enhancing ∆Np63α level in keratinocytes. Therefore, we postulate that exYB-1may either activate Notch or repress EGFR pathways, thus reducing ∆Np63α level which is known to support the proliferative potential of normal and transformed keratinocytes [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was still some evidence that the expression level of hub SFs in tumor tissues was higher than that in normal tissues (Figure 10). The altered expression level of hub SFs has been reported in multiple types of cancer, such as YBX1 (Rossner et al, 2016;Chen et al, 2019), SART1 (Ishida et al, 2000;Sasatomi et al, 2000;Yutani et al, 2001), SNRPE (Tamura et al, 2007;Jia et al, 2011), and SF3B4 (Liu et al, 2018). Other studies have shown that SNRPE (Quidville et al, 2013) and SF3B4 (Shen and Nam, 2018) could develop a new therapeutic agent in cancer.…”
Section: Discussionmentioning
confidence: 98%